Management of carcinoma in situ of the bladder: best practice and recent developments. (December 2015) - Tang, Dominic H.; Chang, Sam S.
Management of carcinoma in situ of the bladder remains a complex and challenging endeavor due to its high rate of recurrence and progression. Although it is typically grouped with other nonmuscle invasive bladder cancers, its higher grade and aggressiveness make it a unique clinical entity. Intravesical bacillus Calmette-Guérin is the standard first-line treatment given its superiority to other agents. However, high rates of bacillus Calmette-Guérin failure highlight the need for additional therapies. Radical cystectomy has traditional been the standard second-line therapy, but additional intravesical therapies may be more appealing for non-surgical candidates and patients refusing cystectomy. The subject of this review is the treatment strategies and available therapies currently available for carcinoma in situ of the bladder. It discusses alternative intravesical treatment options for patients whose condition has failed to respond to bacillus Calmette-Guérin therapy and who are unfit or unwilling to undergo cystectomy.